PENGARUH MOTIVASI DALAM MENINGKATKAN PRESTASI KERJA KARYAWANPADA PERUSAHAAN NUSANTARA TROPICAL FARM (NTF) DI LAMPUNG TIMUR (Studi pada Karyawan Bagian Produksi) - Agustian, Didiek Wijaya (Jurnal Manajemen Magister Darmajaya, 2018)
In Nusantara Tropical Farm Company (NTF), there are problems that are lack of motivation given such as giving compensation, incentives or bonuses and attention etc. to the employees. This causes a decrease in employee morale in completing the work that is charged to employees. As for the problem in this research is "Is there any influence between motivation with work achievement of employees at Company Nusantara Tropical Farm (NTF) in Lampung Timur. The purpose of this study is to find out the influence of Motivation with Employee Achievement and the magnitude of the influence of Motivation on Employee Achievement at Nusantara Tropical Farm Company (NTF) in East Lampung. The research method used in analyzing this problem is quantitative analysis and qualitative analysis. In the quantitative analysis the author uses the formula coefficient determinant and product moment correlation. In this writing using two independent variables (Motivation) denoted by the letter (X) and the dependent variable (Achievement work) is denoted by the letter (Y). The sample technique is to determine the number of samples used as research objects. In this study using population techniques referring to the opinion Suharsimi Arikunto where the number of employees in the Company Nusantara Tropical Farm (NTF) is less than 100 that is 56 people in the production. Based on the analysis, it can be concluded as follows: the value of rhitung obtained is 0.819> from the rtabel value at the significance level of 1% = 0.345 and the significant level of 5% = 0.254. This shows the value of 0.19> 0.345; 0.254 or in other words thitung = 0.819 lies between 0.710 to 0.900, then from the product moment correlation is calculated again by using the formula KP (coefficient determinant) to find closeness of relationship between the two variables that is equal to 67.07% which means the existence of a close influence and positive, this means that "the influence of motivation with employee performance has a significant positive effect in Nusantara Tropical Farm (NTF) Company in Lampung Timur.Keywords — Motivation, Work Achievement